Coenzyme Q10 and its effects in the treatment of neurodegenerative diseases - Santos, Graciela Cristina Dos [UNESP]; Antunes, Lusânia Maria Greggi; Santos, Antonio Cardozo Dos; Bianchi, Maria De Lourdes Pires (Universidade de São Paulo, Faculdade de Ciências Farmacêuticas, 2009)
According to clinical and pre-clinical studies, oxidative stress and its consequences may be the cause or, at least, a contributing factor, to a large number of neurodegenerative diseases. These diseases include common and debilitating disorders, characterized by progressive and irreversible loss of neurons in specific regions of the brain. The most common neurodegenerative diseases are Parkinson's disease, Huntington's disease, Alzheimer's disease and amyotrophic lateral sclerosis. Coenzyme Q10 (CoQ10) has been extensively studied since its discovery in 1957. It is a component of the electron transportation chain and participates in aerobic cellular respiration, generating energy in the form of adenosine triphosphate (ATP). The property of CoQ10 to act as an antioxidant or a pro-oxidant, suggests that it also plays an important role in the modulation of redox cellular status under physiological and pathological conditions, also performing a role in the ageing process. In several animal models of neurodegenerative diseases, CoQ10 has shown beneficial effects in reducing disease progression. However, further studies are needed to assess the outcome and effectiveness of CoQ10 before exposing patients to unnecessary health risks at significant costs.

De acordo com estudos clínicos e pré-clínicos, o estresse oxidativo e suas conseqüências podem ser a causa, ou, no mínimo, o fator que contribui para grande número de doenças degenerativas. Estas doenças incluem problemas comuns e debilitantes, caracterizados por perda progressiva e irreversível de neurônios em regiões específicas do cérebro. As doenças degenerativas mais comuns são doença de Parkinson, de Hutington, de Alzheimer e esclerose amiotrófica lateral. A Coenzima Q10 (CoQ10) tem sido intensamente estudada desde sua descoberta, em 1957. É um componente da cadeia de transporte eletrônico e participa da respiração aeróbica celular, gerando energia na forma de trifosfato de adenosina (ATP). A propriedade da CoQ10 de atuar como antioxidante ou pró-oxidante sugere papel importante na modulação do estado redox celular sob condições fisiológicas e patológicas, desempenhando, também, papel no processo de envelhecimento. Em vários modelos animais de doenças neurodegenerativas, a CoQ10 mostrou efeitos benéficos na redução do curso da doença. Entretanto, há necessidade de estudos adicionais para avaliar o efeito e a eficácia da CoQ10 antes de expor os pacientes a riscos de saúde desnecessários e de alto custo.
Keywords: Coenzyme Q10; Antioxidant; Oxidative stress; Neurodegenerative diseases; Coenzima Q10; Antioxidante; Estresse oxidativo; Doenças neurodegenerativas